Assessing the Fragility of Global Trade : The Impact of Localized Supply Shocks Using Network Analysis - Korniyenko, Yevgeniya (IMF Working Papers; Working Paper ;, 2017)
Anecdotal evidence suggests the existence of specific choke points in the global trade network revealed especially after natural disasters (e.g. hard drive components and Thailand flooding, Japanese auto components post-Fukushima, et cetera). Using a highly disaggregated international trade database we assess the spillover effects of supply shocks from the import of specific goods. Our goal is to identify inherent vulnerabilities arising from the composition of a country's import basket and to propose effective mitigation policies. First, using network analysis tools we develop a methodology for evaluating and ranking the supply fragility of individual traded goods. Next, we create a country-level measure to determine each country's supply shock vulnerability based on the composition of their individual import baskets. This measure evaluates the potential negative supply shock spillovers from the import of each good.